2008
DOI: 10.1007/s11552-008-9136-9
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Transfer for Elbow Flexion in Radiation-Induced Brachial Plexopathy: A Case Report

Abstract: Radiation-induced brachial plexopathy is an uncommon but devastating late complication seen in patients receiving radiation therapy to the chest wall and axilla. Treatment options are unfortunately limited. We report a case of a 59-year-old woman treated with radiation therapy for breast cancer 12 years earlier, who presented with loss of elbow flexion and marked shoulder weakness. Electromyogram and intraoperative stimulation of the musculocutaneous nerve branches were consistent with a proximal motor nerve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Nerve transfer also offers potential for reconstruction in otherwise irreparable nerve palsies such as brachial plexus or accessory nerve neuritis or C5, 6 irreparable cervical disc injury. 4,5 In these cell body injuries, a proximal healthy stump is simply not available. Nerve transfers provide a surgical option to restore sensation to the hand after high and brachial plexus injuries in which the proximal nerve stump is unavailable, inaccessible, or too distant.…”
Section: Indicationsmentioning
confidence: 99%
“…Nerve transfer also offers potential for reconstruction in otherwise irreparable nerve palsies such as brachial plexus or accessory nerve neuritis or C5, 6 irreparable cervical disc injury. 4,5 In these cell body injuries, a proximal healthy stump is simply not available. Nerve transfers provide a surgical option to restore sensation to the hand after high and brachial plexus injuries in which the proximal nerve stump is unavailable, inaccessible, or too distant.…”
Section: Indicationsmentioning
confidence: 99%
“…39 In selected individuals, nerve transfer and nerve reconstruction has also been utilized in attempts to improve motor function in patients with radiation plexopathy. 40,41 In a small series, trigeminal nucleotractomy or placement of cervical cord dorsal root entry zone lesions has been proposed to improve refractory pain from radiation plexopathy. 42 However, for the majority of patients, supportive care remains the focus of therapy.…”
Section: Radiation Plexopathymentioning
confidence: 99%
“…The vascular lesions and fibrosis of connective tissues surrounding the brachial plexus may ultimately result in ischemia as well as nerve demyelination. Some degree of recovery following the 3-month use of anticoagulant agents was reported in radiation injuries of peripheral nerves, which may be a support of blood vessel injury (15,16). In addition, our previous experiment demonstrated that basic fibroblast growth factor (bFGF) could protect neurons from late radiation injury in vitro via the ERK1/2 signal transduction pathway, which may identify a new direction in neural regeneration for future research on the mechanism of RIBP (17,18).…”
Section: Discussionmentioning
confidence: 85%